An Understanding of Implicit Followership Toward New Employees' Self-Efficacy: The Mediating Role of Perceived Supervisor Support - Zhang, Wei; Wang, Xue-Jun (Frontiers in Psychology, 2021)
Under turbulent, boundaryless, and Internet age, the characteristics of career sustainability development have shifted from the perspective of development within the organization to the career development track of self-efficacy. New employees usually face the difficult stage of adapting to the new environment and establishing interpersonal relationships with new colleagues. When new employees enter a new organization, they usually have different implicit followership cognitions. However, previous studies usually focused on how the organization and the leader treat new employees, but seldom explores the implicit followership cognitive state of new employees themselves. Based on social exchange theory and social relationship theory, this research integrates employees’ positive and negative implicit followership, perceived supervisor support, workplace friendship, and perceived self-efficacy into a research framework. This study used a questionnaire survey by an online professional survey website. A total of 394 valid questionnaires were collected. Structural equation model (SEM) analysis was carried out and according to the results, new employees’ positive and negative implicit followership significantly affects perceived supervisor support. Furthermore, perceived supervisor support had a significant impact on perceived self-efficacy. Moreover, perceived supervisor support was found in a mediating role between the relationship of implicit followership theories and perceived self-efficacy. Finally, workplace friendship was found to be a significant moderator in the relationship between perceived supervisor support and perceived self-efficacy. Based on the research results, business managers are suggested to pay more attention to new employees' self-cognition of their job roles and enhance the self-efficacy of new employees in the entry stage.